Stability‐indicating HPLC assay for lysine–proline–valine (KPV) in aqueous solutions and skin homogenates. (9th October 2014) - Pawar, Kasturi R.; Mulabagal, Vanisree; Smith, Forrest; Kolli, Chandra S.; Rangari, Vijaya K.; Babu, R. Jayachandra
Abstract A simple, sensitive and stability‐indicating high‐performance liquid chromatographic (HPLC) assay method was developed and validated for a bioactive peptide, lysine–proline–valine (KPV) in aqueous solutions and skin homogenates. Chromatographic separation was achieved on a reversed phase Phenomenex C18 column (4.6 × 250 mm, packed with 5 µm silica particles) with a gradient mobile phase consisting of 0.1% trifluoroacetic acid (TFA) in water (A) and 0.1% TFA in acetonitrile (B). The proposed HPLC method was validated with respect to accuracy, precision, linearity, repeatability, limit of detection (LOD) and limit of quantitation (LOQ). The calibration curve was linear with a correlation coefficient (r) of 0.9999. Relative standard deviation values of accuracy and precision experiments were <2. The LOD and LOQ of KPV were 0.01 and 0.25 µg/mL, respectively. Under stress conditions (acid, alkali and hydrogen peroxide) KPV yielded lys–pro–diketopiperazine as major degradation product, which was identified by flow injection MS analysis. The developed HPLC method was found to be efficient in separating the active peptide from its degradation products generated under various stress conditions. Also, the validated method was able to separate KPV from other peaks arising from endogenous components of the skin homogenate. Copyright © 2014 John Wiley & Sons, Ltd.